Optimized amylolytic enzymes production in Saccharomycopsis fibuligera DSM-70554: An approach to efficient cassava starch utilization - Gonzalez, Claudio Fabricio (2008)
Different nutritional and operative conditions for improving amylolytic enzyme production by the amylolytic yeast Saccharomycopsis fibuligera DSM-70554 were evaluated. Under selected conditions, cassava starch could be efficiently utilized. Culture conditions such as oxygen saturation (50% dissolved oxygen tension), temperature (34 °C) and pH (5.5) showed a significant influence on α-amylase and glucoamylase production. An optimized culture medium (OPT) formulated by the chemostat pulse-shift method, containing yeast extract as the most favorable organic nitrogen source, vitamins and certain salts (MgCl2, MnSO4, CaCl2) allowed to achieve the highest amylolytic enzyme production, thus leading to an optimal liquefaction and saccharification of cassava starch. Tween 80 (0.2–1% w/v) demonstrated to be a favorable amendment for amylolytic enzyme production. Under the conditions herein described, a 97% degradation of cassava starch could be finally attained under batch culture mode. Maximal values of 633.3 U L−1 h−1 of α-amylase and 72.1 U L−1 h−1 of glucoamylase under optimized conditions represented ∼9 and ∼3-fold increments, respectively, as compared to preliminary fermentation assays under non-optimal conditions.